Role of Rb during Neurogenesis and Axonal Guidance in the Developing Olfactory System - Jaafar, Carine; Omais, Saad; Al Lafi, Sawsan; El Jamal, Nadim; Noubani, Mohammad; Skaf, Larissa; Ghanem, Noël (Frontiers in Molecular Neuroscience, 2016)
The Retinoblastoma protein, Rb, was shown to regulate distinct aspects of neurogenesis in the embryonic and adult brain besides its primary role in cell cycle control. It is still unknown, however, whether Rb is required for tissue morphogenesis and the establishment of synaptic connections between adjacent tissues during development. We have investigated here the role of Rb during development of the olfactory system (OS), which heavily relies on reciprocal interactions between the olfactory epithelium (OE) and the olfactory bulb (OB). We show that mice carrying a telencephalic-specific deletion of Rb display several neurogenic defects in the OS during late development. In the OE, loss of Rb leads to ectopic proliferation of late-born progenitors (Tuj-1+), abnormal radial migration and terminal maturation of olfactory sensory neurons (OSNs). In the OB, deletion of Rb causes severe lamination defects with loss of clear boundaries between distinct layers. Importantly, starting around E15.5 when OB glomerulogenesis is initiated, many OSNs axons that project along the olfactory nerve layer (ONL) fail to properly innervate the nascent bulb, thus resulting in partial loss of connectivity between OE-OB and gradual neuronal degeneration in both tissues peaking at birth. This deficiency correlates with deregulated expressions of two key chemo-repellant molecules, Robo2/Slit1 and Nrp2/sema3F that control the formation of dorsal-ventral topographic map of OSNs connections with OB glomeruli. This study highlights a critical requirement for Rb during neurogenesis and the establishment of proper synaptic connections inside the OS during development.